The nature of making: rapid prototyping in architecture - Bacon, Mark (Kansas State University, 2006)
The purpose of this study is to examine how the industrial process of rapid prototyping might reshape practice and making in architecture. Rapid prototyping is defined as an accelerated, adaptive evolution of a system or its components in some form using computer-aided drafting and manufacturing. Historically, all architecture was the intelligence of a single maker—the master builder. Specialization has caused architecture to fragment with architects serving only as designers. This report explores the ability of computer-aided drafting and manufacturing technologies to streamline the design procedure, which potentially increases the architect’s input into the process of building. Effectually, the architect narrows the distance between the design and the built—returning the architect to the role of master builder. An actual design exercise will examine the connection of architectural practice to making. To apply this research a habitable space was constructed through the incorporation of rapid prototyping.
Keywords: Rapid prototyping; Master builder; Computer numerically controlled; Versioning; Architecture (0729)